Garrett on the irrationality of pure time preferences - Joaquin, Jeremiah Joven B. (Animo Repository, 2019)
In “Experience and Time,” Brian Garrett poses a challenge to friends of the rationality of pure time preferences. In this discussion note, we accept the challenge and provide two kinds of cases wherein some pure time preferences could be deemed rational. © 2019, Springer Nature B.V.